Bicuspid Aortic Valve Presenting with Severe Stenosis and Regurgitation - A Case Report with Review - Hasan, Md Nazmul; Siddique, Md Abu; Banerjee, Sajal Krishna; Ahmed, CM; Sheikh, Naveen; Hoque, Md Harisul (University Heart Journal, 2014)
Bicuspid aortic valves (BAV) are cardiac valvular anomaly, occurring in 12% of the general population. It is twice as common in males as in females.In many cases, a bicuspid aortic valve will cause no problems.However BAV may become calcified later in life, which may lead to varying degrees of severity of aortic stenosis that will manifest asmurmurs. If the leaflets do not close correctly, aortic regurgitation can occur. These mixed clinical finding sometimes confuses physician and culminating to considering other differentials, needs further more subsequent investigation and imaging, thus prolonging evaluation time and delaying decision making for treatment plan. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19517 University Heart Journal Vol. 9, No. 1, January 2013; 64-66